Mechanical Properties Enhancement of AZ91 Magnesium Alloy Reinforced with Various Ratios of Titanium Particles and Processed by ECAP - Huang, Song-Jeng; Lee, Yu-Quan; Tanoto, Yopi Yusuf (Journal of Research Updates in Polymer Science, 2023)
This study utilized AZ91 magnesium-aluminum alloy as the matrix for magnesium-based composites, reinforced with micron-sized titanium (Ti). Gravity casting and mechanical stirring were employed to fabricate specimens with 0 wt.%, 0.3 wt.%, and 0.5 wt.% Ti reinforcement. Heat-treated samples underwent Equal Channel Angular Pressing (ECAP), and microstructures were analyzed via SEM and XRD. The experimental results demonstrate that the addition of micron-sized titanium improves the yield strength, ultimate tensile strength, and hardness. The inclusion of 0.5 wt.% titanium powder resulted in a 17.5% increase in ultimate tensile strength and a 37% increase in yield strength. After secondary processing with ECAP, the ultimate tensile strength showed an additional 25% increase, while the yield strength increased by 13.5%. Vickers hardness test results reveal a significant 13.7% strength improvement with the addition of 0.5 wt.% titanium powder, and after ECAP secondary processing, there was a marginal additional increase of 0.8%.